AB0912 Two-year efficacy and safety of guselkumab for treatment of moderate-to-severe psoriasis: phase 3 voyage 1 trial. (12th June 2018) - Griffiths, C.E.; Papp, K.A.; Kimball, A.B.; Randazzo, B.; Wasfi, Y.; Li, S.; Shen, Y.-K.; Blauvelt, A.
Abstract : Background: Guselkumab (GUS) is an interleukin-23 inhibitor recently approved in the US for treatment of moderate-to-severe psoriasis. Objectives: Efficacy and safety data for up to 100 wks of GUS treatment are reported. Methods: In the VOYAGE 1 Phase 3, randomised, double-blind, placebo/active comparator-controlled trial, 837 patients were randomised at baseline to placebo (PBO) at wks0/4/12 then GUS 100 mg at wks16/20 and q8w (n=174); GUS at wks0/4/12, and q8w (n=329); or adalimumab (ADA) 80 mg at wk 0, 40 mg at wk1, and q2w through wk47 then GUS at wk52 and q8w (n=334). Efficacy was assessed using nonresponder imputation through wk48 and treatment failure rules from wks52–100. Results: Among patients randomised to GUS, or PBO→GUS at wk16, efficacy (PASI, Psoriasis Area and Severity Index; IGA, Investigator's Global Assessment) was maintained from wks52–100 with continuous GUS treatment. Among those randomised to ADA (→GUS at wk52), efficacy improved from wks52–100. Similar findings were observed for patient-reported outcomes (PSSD, Psoriasis Symptoms and Signs Diary; DLQI, Dermatology Life Quality Index; table 1). Through wk100, there were no disproportionate increases in rates of Adverse Events (AEs) compared with rates through wk48. Serious AE rates were low and remained stable; no TB, opportunistic infections, or serious hypersensitivity reactions were reported. Conclusions: Efficacy among GUS patients was maintained through 2 years of continuous treatment. Efficacy among ADA→GUS patients improved from wks52–100. GUS was well-tolerated, with a similar safety profile as previously reported. Disclosure of Interest: C. Griffiths Grant/research support from: Janssen Research and Development, LLC, K. Papp Grant/research support from: Janssen Research and Development, LLC, A. Kimball Grant/research support from: Janssen Research and Development, LLC, B. Randazzo Employee of: Janssen Research and Development, LLC, Y. Wasfi Employee of: Janssen Research and Development, LLC, S. Li Employee of: Janssen Research and Development, LLC, Y.-K. Shen Employee of: Janssen Research and Development, LLC, A. Blauvelt Grant/research support from: Janssen Research and Development, LLC